Pelaksanaan Perlindungan terhadap Perempuan Korban Kekerasan dalam Rumah Tangga (Studi di DP3AK dan UPT PPA Provinsi Jawa Timur) - Putri Natasya (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
This study will concentrate on the implementation of the protection provided by the Office of Women's Empowerment, Child Protection and Population of East Java Province (DP3AK East Java Province) through the Technical Implementation Unit for the Protection of Women and Children of East Java Province (UPT PPA East Java Province) for women victims of violence in household. The purpose of this research is to examine how the Implementation of Protection carried out by the DP3AK of East Java Province for women victims of domestic violence and identify the obstacles that must be faced and the efforts made in dealing with these obstacles. This study uses a qualitative data analysis approach and is legal-empirical in nature. Interviews, data collection techniques, and literature analysis were used in this study. Based on the research results, the DP3AK of East Java Province through the management of the UPT PPA of East Java Province carried out the stages of the process of protecting women victims of domestic violence in accordance with the regulations, namely in the Regulation of the Minister of Women's Empowerment and Women's Protection Number 2 of 2022 concerning Service Standards for the Protection of Women and Children. The obstacles faced were the existence of large power relations by the perpetrators, the victims were not open in conveying information, the environment was not good enough, the limited workforce at UPT PPA East Java Province and the limited budget for the implementation of protection for women victims of domestic violence.